2022
DOI: 10.3390/ani12121552
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Level of Dietary Zinc for Newly Weaned Pigs: A Dose-Response Study

Abstract: One hundred and eighty individually housed piglets with an initial body weight of 7.63 ± 0.98 kg (at 28 days of age) were fed a diet containing either 153, 493, 1022, 1601, 2052 or 2407 mg zinc/kg (added Zn as zinc oxide; ZnO) from day 0–21 post weaning to determine the optimal level of Zn for weaned piglets. Body weight, feed intake and faecal scores were recorded, and blood and faecal samples were collected. Dietary Zn content quadratically affected both feed intake and gain in the first two weeks, with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
(88 reference statements)
1
8
2
Order By: Relevance
“…The negative or close to zero ATTD of Zn when supplied at 100 mg added/kg irrespective of Zn source in the present study therefore indicates that on day 14 PW, pigs were under supplied with Zn. This result is well in line with recent results by Hansen et al [ 25 ]. They showed that 150 mg total Zn/kg feed was far from enough to provide weaned pigs the NRC recommended 46.8 mg Zn per day [ 27 ] and also not enough to ensure optimal feed intake, growth and serum Zn status during the first two weeks PW.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The negative or close to zero ATTD of Zn when supplied at 100 mg added/kg irrespective of Zn source in the present study therefore indicates that on day 14 PW, pigs were under supplied with Zn. This result is well in line with recent results by Hansen et al [ 25 ]. They showed that 150 mg total Zn/kg feed was far from enough to provide weaned pigs the NRC recommended 46.8 mg Zn per day [ 27 ] and also not enough to ensure optimal feed intake, growth and serum Zn status during the first two weeks PW.…”
Section: Discussionsupporting
confidence: 94%
“…The average daily feed intake across treatments during the first week PW was slightly lower (118 g/day) than what we have previously observed in individually housed piglets fed similar types of diets (approximately 150 g/day) [ 25 ]. This is most likely caused by the lower initial weight at weaning (average 6.8 kg) compared to pigs in the study by Hansen et al [ 25 ] (7.6 kg).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations